2022
DOI: 10.1158/1078-0432.ccr-22-0931
|View full text |Cite
|
Sign up to set email alerts
|

Detection of BRCA1, BRCA2, and ATM Alterations in Matched Tumor Tissue and Circulating Tumor DNA in Patients with Prostate Cancer Screened in PROfound

Abstract: Purpose: Not all patients with metastatic castration-resistant prostate cancer (mCRPC) have sufficient tumor tissue available for multigene molecular testing. Furthermore, samples may fail because of difficulties within the testing procedure. Optimization of screening techniques may reduce failure rates; however, a need remains for additional testing methods to detect cancers with alterations in homologous recombination repair genes. We evaluated the utility of plasma-derived circulating tumo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…These data are consistent with the prior studies [ 14 , 18 , 19 ]. Tukachinsky and colleagues reported that with tumor tissue as reference, the positive percentage agreement for BRCA1/2 on cfDNA was 93% [ 14 ].…”
Section: Discussionsupporting
confidence: 94%
“…These data are consistent with the prior studies [ 14 , 18 , 19 ]. Tukachinsky and colleagues reported that with tumor tissue as reference, the positive percentage agreement for BRCA1/2 on cfDNA was 93% [ 14 ].…”
Section: Discussionsupporting
confidence: 94%
“…15-20% of mCRPC harbor deleterious HRR-related gene mutations, most commonly in BRCA2, ATM and CDK12. Concordance between tissue and ctDNA for HRR gene mutations is excellent, exceeding 90% in most studies (23,64,71,78,79). However, an HRR-related gene mutation alone may be insufficient to confer therapeutic vulnerability.…”
Section: Homologous Recombination Repair Deficiencymentioning
confidence: 97%
“…These resourcing requirements mean that a majority of clinicians around the world continue to have limited access to ctDNA profiling to inform patient care. Instead, clinicians typically encounter ctDNA testing in the clinical trial setting, where it is increasingly used alongside tumor tissue testing to screen for genomic alterations that may confer sensitivity to established and novel targeted therapies (20)(21)(22)(23)(24)(25). Outside of clinical trials, US FDAapproved commercial platforms are available (e.g., FoundationOne Liquid CDx, Guardant360 CDx) (26, 27), but can be cost prohibitive for patients unable to acquire partial or full financial reimbursement for testing.…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations